2016
DOI: 10.1073/pnas.1522159113
|View full text |Cite
|
Sign up to set email alerts
|

Open complex scrunching before nucleotide addition accounts for the unusual transcription start site of E. coli ribosomal RNA promoters

Abstract: Most Escherichia coli promoters initiate transcription with a purine 7 or 8 nt downstream from the -10 hexamer, but some promoters, including the ribosomal RNA promoter rrnB P1, start 9 nt from the -10 element. We identified promoter and RNA polymerase determinants of this noncanonical rrnB P1 start site using biochemical and genetic approaches including mutational analysis of the promoter, Fe 2+ cleavage assays to monitor template strand positions near the active-site, and Bpa cross-linking to map the path of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 45 publications
(54 reference statements)
4
69
0
Order By: Relevance
“…Increasing the distance between the −10 region and the start site is expected to weaken these contacts, facilitating promoter escape (17). In agreement with recent reports (12, 17), we found that the discriminator, but not other promoter regions, determined the differences in abortive synthesis between the T7A1 and λP R promoters (Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Increasing the distance between the −10 region and the start site is expected to weaken these contacts, facilitating promoter escape (17). In agreement with recent reports (12, 17), we found that the discriminator, but not other promoter regions, determined the differences in abortive synthesis between the T7A1 and λP R promoters (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The discriminator region between the −10 hexamer and the transcription start site (TSS; +1) has recently emerged as an important modulator of the open complex properties (11)(12)(13)(14)(15)(16)(17)(18). In a stable open complex formed by Thermus thermophilus RNAP, the −6 and −5 bases of the discriminator NT strand (NT DISC ) make crucial contacts with σ1.2, and βArg371 (E. coli numbering) interacts with the adjacent −4 and −3 bases (14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1A) (TSS = 6). According to this model, any protein-DNA or proteinprotein interaction that affects the energy landscape for transcription bubble expansion or contraction (scrunching or antiscrunching) in RPo potentially could modulate TSS selection (13,14).…”
mentioning
confidence: 99%